INTRODUCTION. (1st June 2017) - Unknown
Abstract : The opening decades of the twenty-first century have seen a notable revival of interest in the records of the medieval English parliament. In 2004–2005 a team of scholars funded by the Leverhulme Trust and led by Chris Given-Wilson published The Parliament Rolls of Medieval England ( PROME ), a new electronic and print edition, with full translation, of the extant parliament rolls for the reigns of Edward I to Henry VII. Because PROME focuses on those aspects of parliamentary business that were committed to permanent record on the parliament rolls, it does not consider systematically the other available records associated with the medieval parliament. In particular, it does not reproduce the substantial numbers of unenrolled petitions submitted in parliament that were printed in the eighteenth-century edition of the rolls, Rotuli Parliamentorum ( RP ), though it does include introductory materials and appendices providing summaries and transcripts of these and other ancillary documents.